Clinical Characteristics of Hospitalized COVID-19 in Children: Report From the COVID-19 Registry in Japan. (6th September 2021) - Shoji, Kensuke; Akiyama, Takayuki; Tsuzuki, Shinya; Matsunaga, Nobuaki; Asai, Yusuke; Suzuki, Setsuko; Iwamoto, Noriko; Funaki, Takanori; Ohmagari, Norio
Abstract: A total of 1038 pediatric patients with COVID-19 were identified. Among these, 308 (30%) had asymptomatic COVID-19. The overall outcome was good, and no patients died. A significant rate of patients aged <24 months and ≥13 years were found in the symptomatic group.